Analisis Implementasi Kompetensi Profesional Guru Pak Di Era Revolusi Industri 4.0 Dalam Meningkatkan Motivasi Belajar Siswa Di SMP Negeri SATAP 3 Sangalla’ - Trisnawadi Darius (Institut Agama Kristen Negeri Toraja, 2022)
Abstract- This research is motivated by the problems that occur in Junior High School of SATAP 3 Sangalla', teachers especially Christian Religious Education do not yet have creativity in terms of making media and using technology in learning Christian Religious Education which motivates students so that the level of learning motivation of students is still very low. minimal. Therefore, the purpose of this study is to analyze the professional competence of Christian Religious Education teachers in the era of the industrial revolution 4.0 in increasing students' learning motivation at Junior High School of SATAP 3 Sangalla'. To get the results of the research objectives used descriptive qualitative methods with data collection techniques through literature study, observation, and interviews. The results of this study indicate that the professional competence of Christian Religious Education teachers in the era of the industrial revolution 4.0 in increasing student learning motivation at Junior High School of SATAP 3 Sangalla' is still very much needed by involving technology in the process of teaching, educating, training, assisting, directing and assessing students. The presence of Christian Religious Education teachers at Junior High School of SATAP 3 Sangalla' in the learning process still does not involve the use of technology so that it triggers a lack of student motivation. Therefore, teacher of Christian Religious Education must improve their professional competence in the 4.0 era by honing their ability to use technology to support classroom teaching because it can increase student learning motivation. Keywords:; Christian Religious Education Teacher, Industrial Revolution 4.0, Motivation, Professional Competence, Study. Kata kunci: Belajar, Guru PAK, Kompetensi Profesional, Motivasi, Revolusi Industri 4.0.